The Role of Parents in Parenting from Islamic Law Perspectives: A Study of Muslim Families in Ambang II Village - M. Alimashariyanto; Suprijati Sarib; Sabil Mokodenseho (At-turas: Jurnal Studi Keislaman)
This study aims to analyze the role of parents in the upbringing of children from the perspective of Islamic law. The focus of this study is important because children are the next generation, and the embodiment of the future, so they must be nurtured because they are vulnerable to being affected by negative things. In addition, parents have a responsibility for the growth and development of children. The qualitative descriptive method was used to analyze the data. Research data were obtained from informants through interview and documentation techniques, in addition to written sources from books and journal articles. The results showed that parents in parenting activities do not only raise children but educate, guide, and protect children from childhood to adulthood in accordance with the values, norms, and culture adopted in the family and society. The choice of democratic, authoritarian, and permissive parenting in parenting activities has implications for the formation of the socio-religious spirit of children in society in a better direction. In conclusion, the role of parents in every stage and development of children is very necessary while considering the use of appropriate parenting patterns.